Changes in CYP2C19 enzyme activity evaluated by the [13C]-pantoprazole breath test after co-administration of clopidogrel and proton pump inhibitors following percutaneous coronary intervention and correlation to platelet reactivity. (27th January 2016) - Harvey, Adrien; Modak, Anil; Déry, Ugo; Roy, Mélanie; Rinfret, Stéphane; Bertrand, Olivier F; Larose, Éric; Rodés-Cabau, Josep; Barbeau, Gérald; Gleeton, Onil; Nguyen, Can Manh; Proulx, Guy; et al.
Abstract: Dual antiplatelet therapy (DAPT) with clopidogrel and aspirin is used for the prevention of cardiovascular events following percutaneous coronary intervention (PCI). These agents increase the risk of gastrointestinal bleeding. To prevent these events, proton pump inhibitors (PPI) are routinely prescribed. It has been reported that with the exception of pantoprazole and dexlanzoprazole, PPIs can impede conversion of clopidogrel by cytochrome P450 2C19 (CYP2C19) to its active metabolite, a critical step required for clopidogrel efficacy. Changes in CYP2C19 enzyme activity (phenotype) and its correlation with platelet reactivity following PPI therapy has not yet been fully described. In this study we attempted to determine if the [ 13 C ]-pantoprazole breath test (Ptz-BT) can evaluate changes in CYP2C19 enzyme activity (phenoconversion) following the administration of PPI in coronary artery disease (CAD) patients treated with DAPT after PCI. Thirty (30) days after successful PCI with stent placement, 59 patients enrolled in the Evaluation of the Influence of Statins and Proton Pump Inhibitors on Clopidogrel Antiplatelet Effects (SPICE) trial (ClinicalTrials.gov Identifier: NCT00930670) were recruited to participate in this sub study. Patients were randomized to one of 4 antacid therapies (omeprazole, esomeprazole. pantoprazole or ranitidine). Subjects were administered the Ptz-BT and platelet function was evaluated by vasodilator-stimulated phosphoprotein (VASP) phosphorylation and light transmittance aggregometry before and 30 d after treatment with antacid therapy. Patients randomized to esomeprazole and omeprazole had greater high on-treatment platelet reactivity and lowering of CYP2C19 enzyme activity at Day 60 after 30 d of PPI therapy. Patients randomized to ranitidine and pantoprazole did not show any changes in platelet activity or CYP 2C19 enzyme activity. In patients treated with esomeprazole and omeprazole, changes in CYP2C19 enzyme activity (phenoconversion) correlated well with changes in platelet reactivity. Co-administration of omeprazole or esomeprazole in patients treated with clopidogrel results in lower CYP2C19 enzyme activity and increased platelet reactivity as measured by VASP phosphorylation test while patients given pantoprazole or ranitidine did not show any significant changes in CYP2C19 enzyme activity and platelet reactivity.